Influence of High Pass Filter Settings on Motor Evoked Potentials - Nikolov, Petyo; Hassan, Shady S.; Schnitzler, Alfons; Groiss, Stefan J. (Frontiers in Neuroscience, 2021)
Abstract Objective: Motor evoked potentials (MEP), obtained by transcranial magnetic stimulation (TMS) are a common tool in clinical research and diagnostic. Nevertheless, reports regarding the influence of filter settings on MEP are sparse. Here, we compared MEP amplitudes and signal to noise ratio (SNR) using multiple high pass filter (HPF) and notch filter settings. Methods: Twenty healthy subjects were enrolled in the study. Recruitment curves were obtained with HPF settings varied at 10, 20, 50 and 100Hz. The four HPF settings were tested both with and without 50Hz active notch filter. Low pass filter was kept constant at 5kHz. Results: MEP amplitudes with HPF at 10Hz and 20Hz were significantly higher than at 100Hz, regardless of the notch filter. However, SNR did not differ among HPF settings. An active notch filter significantly improved SNR. Conclusions: The reduction in MEP amplitudes with HPF above 20Hz may be due to noise reduction, since the different HPF conditions did not alter SNR. Thus, higher HPF above 50Hz may be an option to reduce noise, the use of a notch filter may even improve SNR. Significance: Our findings are relevant for the selection of filter settings and might be of importance to any researcher who utilizes TMS-MEP.